Distributed RRM for 5G Multi-RAT Multiconnectivity Networks - Monteiro, Victor Farias; Sousa, Diego Aguiar; Maciel, Tarcisio Ferreira; Cavalcanti, Francisco Rodrigo Porto; Silva, Carlos F. M. e; Rodrigues, Emanuel Bezerra (IEEE systems journal, 2019)
A tight interworking between the next generation of wireless cellular networks, the fifth generation (5G), and legacy standards, e.g., long term evaluation (LTE), is being envisioned in order to support a wide range of service requirements. Aiming at addressing the challenge of coordinating resources across different technologies, centralized processing units are being considered. However, they have practical issues, e.g., processing costs and increased signaling overhead. In this context, this work formulates an optimization problem in order to manage resources in a multi radio access technology (RAT) scenario. Its objective is to maximize the minimum user throughput in the system subject to the constraint that for each user, his throughput must be higher than a requirement. One of the differences from previous works is that the users may connect to more than one RAT at the same time, the so-called dual connectivity. The referred problem is nonlinear and hard to solve. However, we get to transform it into a simpler form, a mixed integer linear programming, which can be optimally solved using standard optimization methods. This solution is categorized as a centralized solution. Thus, we propose a distributed framework to overcome the drawbacks of centralized processing. This framework is divided into two parts: a base station (BS) selection procedure (performed by the users) and a resource assignment algorithm (performed by the BSs). Besides, a performance evaluation is conducted, considering fourth generation LTE and 5G new radio parameters.